2018
DOI: 10.21511/bbs.13(3).2018.10
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of bank profitability: Islamic versus conventional banks

Abstract: This research analyzes the determinants of bank profitability by investigating the internal factors that affect the profitability of Islamic banks and conventional banks. It then compares the results from the two types in order to understand how they differ from each other. As previous researchers focus on either Islamic or conventional banks, this research will analyze both by comparing how they are each influenced by profitability factors. Few researches have attempted to compare the profitability of Islamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 8 publications
2
29
0
3
Order By: Relevance
“…This is in accordance with the economics of scale which states that larger companies will be able to lower their operating costs (Adelopo, Lloydking & Tauringana, 2018). Previous research shows that the size of Islamic banks has a positive impact on profitability (Alzoubi, 2018;Alharbi, 2017). Islamic banks have a better chance in a diversified portfolio of investments and assets.…”
Section: Sizesupporting
confidence: 79%
“…This is in accordance with the economics of scale which states that larger companies will be able to lower their operating costs (Adelopo, Lloydking & Tauringana, 2018). Previous research shows that the size of Islamic banks has a positive impact on profitability (Alzoubi, 2018;Alharbi, 2017). Islamic banks have a better chance in a diversified portfolio of investments and assets.…”
Section: Sizesupporting
confidence: 79%
“…This result supports the conclusion from the research by Alarussi & Alhaderi (2018) which explained that the FDR has no significant effect on the banking profitability in Malaysia. In contrast, Sriyana (2015), Alzoubi (2018) and Sudarsono (2017) stated that FDR statistically affecting the Islamic banks' profitability ratio.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, there is a tendency for national authorities to attempt to improve the profitability of the banking sector and its efficiency. Alzoubi (2018) and Yao et al (2018) indicated that banks' profitability has several determinants, such as size, capital, risk, etc. Each variable has a different relationship with profitability.…”
Section: The Interplay Between the Liquidity Coverage Ratio Requirements And Banks' Profitabilitymentioning
confidence: 99%
“…This variable provides a source of funding to banks and, thus, it evaluates the capital adequacy. Based on Alzoubi (2018), bank capital is measured as the total equity to total assets. In terms of the relationship between bank capital and profitability, it is suggested that, when the assumption of a perfect market is lightened, a rise in capital would lower the costs related to bankruptcy and financial crises and therefore, banks would be more profitable.…”
Section: Bank Capital (Cap)mentioning
confidence: 99%
See 1 more Smart Citation